Investigating the effect of decontaminants on microbiological and chemical properties of rainbow trouts - Dikici, Abdullah; Ozpolat, Emine; Bozatli, Sumeyye Betul; Koluman, Ahmet; Patir, Bahri; Calicioglu, Mehmet (Tubitak Scientific & Technological Research Council Turkey, 2021)
This study was designed to determine the effect of decontamination on the shelf life of whole rainbow trouts. For this purpose 0.5% cetylpyridinium chloride (CPC), 10% trisodium phosphate (TSP), 2.5% acetic acid (AA), 2.5% lactic acid (LA), 1200 ppm acidified sodium chloride (ASC) and control (tap water) were used as decontaminants. After the decontamination process, the samples were stored in cold storage and subjected to microbiological and chemical analyzes on days 0, 3, 6, 9, 12 and 15. Mesophilic bacteria, psychrophilic bacteria, lactic acid bacteria, Pseudomonas spp., Enterobacteriaceae and coliform bacteria were enumerated for the evaluation of microbiological quality, whereas pH, total volatile alkaline nitrogen (TVB-N), thiobarbituric acid (TBA) were determined for the evaluation of the chemical quality of fish samples. The study was repeated 3 times and 6 fish were used in each group corresponding to 108 fish in total. Microbiological samples were evaluated with a modification in USDA/FSIS chicken carcass method. The data of microbiological analysis showed that decontamination provided a significant improvement on the microbiological quality and the decontaminants used in this study extended the microbiological shelf life of rainbow trout. However, acidic decontaminants and TSP caused some changes in the physical properties of rainbow trouts. On the other hand, the use of CPC extended the shelf life of rainbow trouts without adversely affecting the texture. The microbiological sampling protocol used in this study was proved to be easier to apply and gave coherent results.
Keywords: Fish; organic acid; trisodium phosphate; cetylpyridinium chloride; shelf life